The Distorted Image of Prophet Muhammad in Percy's Mahomet and His Heaven (1601) - Al-Olaqi, Fahd Mohammed Taleb (Advances in Social Sciences Research Journal, 2017)
The article critiques the portrayal image of Prophet Muhammad in William Percy's Mahomet and His Heaven (1601) (Note: 1). The play is marked with anti-Mahomet prejudice expressed in willful attempts to devalue Prophet Muhammad in order to avert the English public from Islam. The story of Haroth and Maroth in the Noble Qur’ān is misused to vilify Islam and its Prophet. Percy pinpoints some unscrupulous and offensive characterization to Prophet Muhammad to blame him for the establishment of a competitive Islamic world to Christendom. Thus, Percy exemplifies the typical Elizabethan sense of the delight in defaming Islam and Prophet Muhammad. Like Percy, some Elizabethan dramatists attacked the religious symbols of the Ottoman Islamic World to defend European Christian values. The Elizabethan hostility and anti-sentiment towards the Ottoman Empire was sceptical to the Islamic multicultural integration. The scenes of Medieval Christian polemical accounts are reproduced in dealing with Islamic theology, fallacy, prophecy, and characterization.